Pelaksanaan Kampus Mengajar Angkatan 1 Program Merdeka Belajar Kampus Merdeka di Sekolah Dasar - Rosyida Nurul Anwar (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2021)
The teaching campus provides opportunities for students to hone their leadership and character and have a learning experience. The campus teaching program is expected to increase the effectiveness of the learning process in the emergency conditions of the Covid-19 pandemic. Through the campus teaching program, students have activities that are responsible for assisting learning activities, assisting technology adaptation, and assisting administration at the school where they are assigned. This study aimed to find out how the implementation of campus teaching at Muhammadiyah 1 Padas Elementary School. The research method uses descriptive qualitative. Data collection techniques using observation, interviews and documentation. The data collected was then processed using qualitative data processing techniques from Miles & Huberman. The study results indicate that the implementation of the campus teaching program batch 1 in 2021 at Muhammadiyah 1 Padas Elementary School includes; First, teaching, which consists of face-to-face learning, home visits, and online learning. Second, technology adaptation by assisting teachers in making teaching media and teaching materials by the curriculum. Third, the administration is also carried out with students assisting teachers in preparing learning tools as administrative completeness. The implementation of the teaching campus can provide experience and empower students and have a positive impact on students in the COVID-19 situation.